2021
DOI: 10.3389/fvets.2021.629016
|View full text |Cite
|
Sign up to set email alerts
|

Pelleting of a Total Mixed Ration Affects Growth Performance of Fattening Lambs

Abstract: Feeding pelleted total mixed rations (TMR) instead of traditional loose concentrate plus forage to fattening lambs is an emerging practice. This study aimed to determine the effects of feeding pelleted TMR to fattening lambs on feed intake behaviour, growth performance, feed digestion, rumen fermentation characteristics, rumen microbial community, serum parameters, slaughter performance, meat quality, and the economic outcome. Two physical forms (pelleted vs. un-pelleted) of TMR composed of the same ingredient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
4
31
0
Order By: Relevance
“…The dose of YC at the 5 g/kg diet was recommended by the YC producer. The proportion of corn at the 350 g/kg diet was recommended by researchers ( 23 ), and the high proportion (600 g corn/kg diet) is used by farmers in the region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of YC at the 5 g/kg diet was recommended by the YC producer. The proportion of corn at the 350 g/kg diet was recommended by researchers ( 23 ), and the high proportion (600 g corn/kg diet) is used by farmers in the region.…”
Section: Methodsmentioning
confidence: 99%
“…Feeding total mixed rations (TMR) has been popular due to its advantages of providing balanced nutrients in the diet, the relatively stable rumen environment, reduced feed sorting, and better animal performance in dairy cows (15). TMR feeding has been further developed by pelleting the TMR and fed to cattle (16)(17)(18) and sheep (19)(20)(21)(22)(23). Feeding of a pelleted TMR results in almost no feed selection by animals, non-palatable ingredients can be included in the diet, minimisation of feed loss during storage and feeding, and improved ease of feeding management and labour efficiency (11).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of lamb breeding programs with increased productivity, feeding of the animals with pelleted concentrates has been promoted and implemented in many modern fattening systems ( Islam et al, 2017 ). Recently, accumulating evidence has indicated that the application of pelleted concentrates is an effective method to avoid selective eating, reduce nutrition wastage during storage and feeding, save labor, and increase rearing profitability ( Blanco et al, 2015 ; Zhong et al, 2018 ; Li et al, 2021b ). Previous studies have demonstrated that pelleted HG diets improve rumen fermentation and amplify the use of simple sugars by rumen microbiota ( Trabi et al, 2019 ), although information regarding the impact of pelleted HG diets on the small intestine is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative growth performance study in goats and lambs on feeding crop residue-based complete mash Vs complete pellet feed was studied by Li et al, [6]. Final body weight (Kg), ADG(g/d) and daily feed intake (Kg DM) was significantly higher and feed to gain ratio was better in goats and lambs fed pelleted crop residue based complete feed than complete mash feed.…”
Section: Comparative Study Of the Effect Of Feeding The Complete Feed In Various Formsmentioning
confidence: 99%